Enhancing the understanding of coinfection outcomes: Impact of natural atypical porcine pestivirus infection on porcine reproductive and respiratory syndrome in pigs - Hill, Holly (2024)
Atypical porcine pestivirus (APPV) is a novel member of the Pestivirus genus detected in association with congenital tremor (CT) type A-II outbreaks and from apparently healthy pigs, both as singular infection and as part of multi-pathogen infections. 'Classical' pestiviruses are known to cause immunosuppression of their host, which can increase susceptibility to secondary infections, severely impacting health, welfare, and production. To investigate APPV's effect on the host's immune system and characterise disease outcomes, 12 piglets from a natural APPV CT type A-II outbreak were experimentally infected with porcine reproductive and respiratory syndrome virus (PRRSV), a significant porcine pathogen. Rectal temperatures indicating febrile responses, viremia and viral-specific humoral and cellular responses were assessed throughout the study. Pathological assessment of the lungs and APPV-PRRSV co-localisation within the lungs was performed at necropsy. Viral co-localisation and pathological assessment of the lungs (Immunohistochemistry, BaseScope in situ hybridisation) were performed post-mortem. APPV status did not impact virological or immunological differences in PRRSV-infected groups. However, significantly higher rectal temperatures were observed in the APPV+ve/PRRSV+ve group over four days, indicating APPV increased the febrile response. Significant differences in the lung consolidation of the apical and intermediate lobes were also present, suggesting that APPV co-infection may augment lung pathology.